Real-Time Monitoring of the Nucleation and Growth of ZnO Nanoparticles Using an Optical Hyper-Rayleigh Scattering Method - Segets, Doris; Martinez Tomalino, Lars-Owe; Gradl, Johannes; Peukert, Wolfgang (Journal of Physical Chemistry C, 2009)
Incoherent nonlinear hyper-Rayleigh scattering (HRS) has been applied to monitor the different stages in the synthesis of sub-10 nm ZnO nanoparticles. During time-resolved investigation of the ripening process, we measured an increase in the particle hyperpolarizability, βZnO, with increasing particle size. Millisecond time resolution measurements revealed regions of prevalent nucleation, growth, and ripening. Using the size-dependent hyperpolarizabilities, a new general approach is introduced for the quantitative determination of nucleation, growth, and ripening rates via in situ HRS measurements. The derived solubility also allowed the determination of reasonable values of the ZnO surface energy.